2010
DOI: 10.5858/2009-0292-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 Mutations at Diagnosis and Relapse in Acute Myeloid Leukemia: Cytogenetic and Pathologic Correlations, Including Cuplike Blast Morphology

Abstract: Context.—Acquired mutations in the fms-like tyrosine kinase 3 gene (FLT3) adversely impact relapse risk after chemotherapy in patients with acute myeloid leukemia (AML). The FLT3 mutation status may differ at diagnosis and relapse, suggesting a potential role in chemoresistance, yet few reports have addressed the cytogenetic and pathologic correlates of FLT3 mutations in relapsed AML. Objectives.—To determine FLT3 mutations at diagnosis and relapse in a cohort of adult patients with chemoresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Grag et al indicated that the incidence of somatic mutations in FLT-3 is not enough for AML development, and other genetic factors are required to convert a myeloid progenitor into leukemic cells 18 . In another study, FLT-3 mutations were reported in relapsed AML patients and not in newly diagnosed patients 19 . In contrast, we found that among 41 newly diagnosed AML patients, 19 patients (46.34%) displayed over-expressed FLT-3.…”
Section: Discussionmentioning
confidence: 93%
“…Grag et al indicated that the incidence of somatic mutations in FLT-3 is not enough for AML development, and other genetic factors are required to convert a myeloid progenitor into leukemic cells 18 . In another study, FLT-3 mutations were reported in relapsed AML patients and not in newly diagnosed patients 19 . In contrast, we found that among 41 newly diagnosed AML patients, 19 patients (46.34%) displayed over-expressed FLT-3.…”
Section: Discussionmentioning
confidence: 93%
“…Comparative analyses of AML samples from patients at diagnosis and relapse have shown that FLT3-ITD mutations that were originally undetectable at diagnosis can become detectable later at relapse, suggesting that clones with FLT3-ITD mutations may undergo clonal expansion and become a dominant population at relapse after the selective pressure of chemotherapy. [27][28][29][30] Indeed, primary samples from relapsed AML patients demonstrated more significant sensitivity to FLT3 inhibitors than samples obtained from AML patients at diagnosis in vitro, suggesting that AML cells at relapse are more dependent on FLT3 signaling. 31 In addition, patients who had new FLT3-ITD mutation at relapse were shown to have shorter overall survival, 32 as well as significantly worse prognosis even after allogenic hematopoietic stem cell transplant (alloHSCT) than those who maintained wild-type FLT3.…”
Section: Flt3 Mutations In Amlmentioning
confidence: 99%
“…However, other patterns have also been observed during the progression of the disease from diagnosis to relapse. Nearly 20% of patients with AML acquire either a newly detectable FLT3-ITD or FLT3-TKD mutation at relapse or lose the FLT3 mutation from the time of diagnosis [64].…”
Section: Flt3mentioning
confidence: 99%